Assessment of organic matter preservation and soil organic carbon sequestration potential in the Kulapis Formation, Telupid, Sabah - Mohd Al-Farid Abraham; Siti Nur Anisa Mohamad Maidin; Mohd Sani Sarjadi; Baba Musta (Faculty of Science & Natural Resources, UMS, 2024)
The Kulapis Formation in eastern Sabah, comprising red to orange friable sublitharenites, calcareous lithic arenites, and laminated red mudstones, represents a key Paleogene geological structure along the Telupid-Sandakan, Sabah. Despite limited fossil evidence complicating its depositional history, geochemical analysis suggests a deep-water clastic origin. This study, conducted at the Segaliud Lokan Forest Reserve and Sabah Pan Borneo Work-Project 29 outcrops (OC), investigates organic matter (OM) preservation and soil organic carbon (SOC) sequestration potential through CHNS elemental analysis. The multivariate Principal Component Analysis (PCA), explaining 67.2% of the data variability, identifies three distinct depositional clusters: terrestrial, marine, and transitional, emphasizing the significant environmental influences on OM composition. As such, terrestrial-derived samples (OC4), exhibit high carbon content (10.55%) and C/N ratios (31.58), indicative of plant-derived OM stabilized by anoxic conditions and diagenetic alteration. Marine-derived samples (OC1–OC5) show lower carbon concentrations (0.05%–1.03%) and moderate H/C ratios (0.11–0.91), consistent with marine-derived OM and varying maturation levels. Transitional-derived samples (OC6–OC8) display mixed signatures, reflecting dynamic depositional settings with moderate carbon contents (1.38%–4.34%). The SOC sequestration potential ranges widely from 2.1 to 66.17 Mg C/ha, influenced by OM preservation condition and soil texture. Fine sands demonstrate reduced stabilization, while silty clays enhance carbon retention. Exceptionally high SOC in some coarse-textured samples highlights localized depositional conditions favoring carbon preservation. These findings underscore the Kulapis Formation’s heterogeneous carbon dynamics and highlight its role in natural carbon sequestration, offering insights into soil organic carbon retention mechanisms and climate change mitigation.